2016
DOI: 10.1039/c6sc03457h
|View full text |Cite
|
Sign up to set email alerts
|

Solvation and surface effects on polymorph stabilities at the nanoscale

Abstract: We explore the effects of particle size and solvent environment on the thermodynamic stability of two pairs of polymorphs subjected to ball-mill neat grinding (NG) and liquid assisted grinding (LAG).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
221
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(237 citation statements)
references
References 53 publications
14
221
0
2
Order By: Relevance
“…[21,25] The results that we present here suggest that this holds also at high pressure. [21,25] The results that we present here suggest that this holds also at high pressure.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…[21,25] The results that we present here suggest that this holds also at high pressure. [21,25] The results that we present here suggest that this holds also at high pressure.…”
supporting
confidence: 67%
“…[22] LAG, at echnique which consists of grinding solid materials in the presence of af ew drops of solvent, has dramatically broadened the applications of mechanochemistry; [23] LAG often accelerates reactionk inetics and indeed sometimes yields different outcomes to NG techniques. [21,25] The reactiony ield is 50 %i ns olution,w hereas it is over 97 %u nder mechanochemical conditions. The former was generated under ball-mill NG conditions, whereas polymorph Bw as formed under ball-mill LAG conditions where a few drops of MeCN (> 23 mLp er 200 mg) were added to the powder.…”
mentioning
confidence: 99%
“…31 These were rationalised by considering solvent-dependent surface energies relative to the bulk lattice energy. The effect that size can have on the relative stability of nuclei of different forms comes out clearly from consideration of the nano-cluster modelling of inorganic oxides (DOI: 10.1039/c8fd00060c).…”
Section: Csp_thd; Defining the Crystal Energy Landscapementioning
confidence: 99%
“…Ex situ analysis has demonstrated that the type of mechanical treatment [14,24,25], the addition of liquid [14,26,27], a polymer [28,29] and starting polymorph [14] can all play a role in determining the outcome of a polymorphic transformation. This phenomenon is of particular importance to industry, where the solid form of a material is vital to the integrity of its function and the legalities that surround its applications.…”
Section: Introductionmentioning
confidence: 99%